2010
DOI: 10.11646/zootaxa.2557.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Lepidocephalichthys (Teleostei: Cobitidae) with distinctive sexual dimorphism and comments on relationships in southern lineages of Cobitidae

Abstract: Lepidocephalichthys (Telostei:Cobitidae) is diagnosed as being unique among cobitids in having the 7–8th pectoral rays of mature males modified. Recently collected material from Thailand included a new species of Lepidocephalichthys in which mature males have a large (extending over ~75% of the fin-ray length) dorsally projecting and serrated flange and a ventrally projecting flange. The ventrally projecting structure is unique among cobitids. An expanded phylogenetic analysis of cobitids, including previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Along these lines, some have suggested that sequencing and analyzing the entire mitogenome for particular phylogenetic questions is akin to pseudoreplication [13] . Furthermore, numerous studies have relied on single mt genes to infer evolutionary relationships (e.g., [14] ) and the mt gene cytochrome oxidase subunit 1 (COX1) was recommended as the genetic marker for metazoan DNA barcoding [15] , [16] and has been embraced by the Consortium for the Barcode of Life ( http://www.barcodeoflife.org/ ). In this context and given that data from mt genes will continue to play a significant role in various biological disciplines, it is essential to: 1) identify whether each mt gene possesses the same phylogenetic signal and is thus interchangeable; 2) distinguish if particular genes perform better at representing the phylogenetic signal of the entire mitogenome; 3) determine just how many genes might be required to recreate the same topology as inferred from the complete mitogenome; and 4) establish whether any trends in #1–3 are lineage specific or can be generalized across metazoans.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, some have suggested that sequencing and analyzing the entire mitogenome for particular phylogenetic questions is akin to pseudoreplication [13] . Furthermore, numerous studies have relied on single mt genes to infer evolutionary relationships (e.g., [14] ) and the mt gene cytochrome oxidase subunit 1 (COX1) was recommended as the genetic marker for metazoan DNA barcoding [15] , [16] and has been embraced by the Consortium for the Barcode of Life ( http://www.barcodeoflife.org/ ). In this context and given that data from mt genes will continue to play a significant role in various biological disciplines, it is essential to: 1) identify whether each mt gene possesses the same phylogenetic signal and is thus interchangeable; 2) distinguish if particular genes perform better at representing the phylogenetic signal of the entire mitogenome; 3) determine just how many genes might be required to recreate the same topology as inferred from the complete mitogenome; and 4) establish whether any trends in #1–3 are lineage specific or can be generalized across metazoans.…”
Section: Introductionmentioning
confidence: 99%
“…All individuals were identified at the species level, enumerated, and released downstream from their capture site to avoid fish re-capturing. Since some individuals could not be identified in the field, they were first overdosed in clove oil and were preserved in 10% formalin for later identification to the species using a stereo microscope according to the taxonomic keys based on the Catalog of Fish, California [35] and a number of other publication sources [16][17][18][19][20][21][22][23][36][37][38][39][40][41].…”
Section: Fish Samples Species Richness and Relative Abundancementioning
confidence: 99%
“…The study of balitorid loaches was first reported by Smith [15], and subsequently, most studies with a specific emphasis on species identification and classification were performed [16]. As recently as a decade ago, many balitorid species in Thailand have been revised and described as new species [17][18][19][20][21][22][23]. In contrast, the ecological studies of Thai balitorids are limited in the central regions, and to our best knowledge, there are only two publications in balitoridae distribution and their habitats [24,25].…”
Section: Introductionmentioning
confidence: 99%